Pyomyositis in an Immunocompetent Patient Following Gardening Activity - Aliya Rehman DO; Ayoola Olayiwola MD; Christine A. Vu PharmD; Parjanya Bhatt MD; Joelle-Ann Joseph MS; Folusakin Ayoade MD (SAGE Publishing, 2024)
Nocardia pyomyositis in immunocompetent patients is a rare occurrence. The diagnosis may be missed or delayed with the risk of progressive infection and suboptimal or inappropriate treatment. We present the case of a 48-year-old immunocompetent firefighter diagnosed with pyomyositis caused by Nocardia brasiliensis acquired by direct skin inoculation from gardening activity. The patient developed a painful swelling on his right forearm that rapidly progressed proximally and deeper into the underlying muscle layer. Ultrasound imaging of his right forearm showed a 7-mm subcutaneous fluid collection with surrounding edema. Microbiologic analysis of the draining pus was confirmed to be N brasiliensis by Matrix-Assisted Laser Desorption/Ionization Time-of-Flight (MALDI-TOF) Mass Spectrometry. After incision and drainage deep to the muscle layer to evacuate the abscess and a few ineffective antibiotic options, the patient was treated with intravenous ceftriaxone and oral linezolid for 6 weeks. He was then de-escalated to oral moxifloxacin for an additional 4 months to complete a total antibiotic treatment duration of 6 months. The wound healed satisfactorily and was completely closed by the fourth month of antibiotic therapy. Six months after discontinuation of antibiotics, the patient continued to do well with complete resolution of the infection. In this article, we discussed the risk factors for Nocardia in immunocompetent settings, the occupational risks for Nocardia in our index patient, and the challenges encountered with diagnosis and treatment. Nocardia should be included in the differential diagnosis of cutaneous infections, particularly if there is no improvement of "cellulitis" with traditional antimicrobial regimens and the infection extends into the deeper muscle tissues.